Nanocrystalline glass-like carbon thin films may be an useful tool in nerve cells regeneration - Rodríguez-Losada, Noela; Romero, Pablo; Guzmán de Villoria, Roberto; Aguirre-Gómez, José Ángel (My University, 2017)
The interest in carbon nanomaterials with high transparency and electrical conductivity has grown within the last decade in view of a wide variety of applications, including biocompatible sensors, diagnostic devices and bioelectronic implants. The aim of this work is to test the biocompatibility of particular nanometer-thin nanocrystalline glass-like carbon films (NGLC), a disordered structure of graphene flakes joined by carbon matrix
Abstract en el libro de Abstract de la International Conference, p. 99
Keywords: Materiales biomédicos; Biocompatibilidad; Glass-like carbon; SN4741 cell line; Biocompatibility